Break Even Point analysis of liquefied natural gas process and optimization of its refrigeration cycles with technical and economic considerations. (15th December 2021) - Cao, Yan; Mohammadian, Mehrnoush; Pirouzfar, Vahid; Su, Chia-Hung; Khan, Afrasyab
Abstract: Natural gas liquefaction is an expensive process with high energy consumption. Higher mini-LNG capacities have high capital and operating costs meanwhile that will have more product and profit. Therefore, one of the main concerns for the construction on Liquefied Natural Gas (LNG) plants is the optimization of capacities with economic tradeoff for minimizing the cost. In this paper, the mini- LNG production units are simulated in Aspen HYSYS and then in different capacities of the unit, using Aspen Capital Cost Estimator software, economic analysis is implemented. Also, this work focused on the cost optimization for various processes with different capacities. The simulation variable in this simulation is unit capacity, which is performed in capacities of 500, 750, 1000, 1250 and 1500 metric tons per day. For each capacity, the capital cost (CAPEX) and operating cost (OPEX) are evaluated. Finally, the Break Even Point (BEP) and optimum capacity for these mini-LNG plants is obtained. Highlights: Various Mini-LNG process has been simulated, integrated and evaluated using Aspen HYSYS and Aspen capital cost estimation. The different capacity of liquefaction has been compared to find BEP and related CAPEX and OPEX. This approach increases cycle efficiency, decreases energy and cost consumption with lower environmental impact.